Trakai Castle Court Acts of 1660–1661: Typological and Language Characteristics - Ušinskienė, Viktorija (Vilnius University Open Series, 2021)
The paper deals with the local court records of the Grand Duchy of Lithuania (GDL) from the collection of Vilnius University. The study of Trakai Castle Court documentation of 1660‒1661 (F7–TPT, 1660‒1661) allows us to conclude that the chancery work in local courts in the GDL was highly developed at the time. The system of documents’ drawing up and registering was clearly regulated and structured, taking into account the needs of state and public life. Almost all types of court records were composed according to well-defined canons, owing to which we can speak about certain genres of legal documentation that had developed apparently by the end of the 16th and the middle of the 17th centuries. The manuscript written in Polish and Ruthenian languages is important for research of Lithuanian, Polish and Byelorussian history. The abundance of accumulated information enables us to consider it as unique reference book that reflects changing sociolinguistic situation of the GDL. From the middle of the 17th century, Polish starts to significantly dominate in legal documentation, thus forces Ruthenian out of court by the end of the century.
Keywords: court books of the Grand Duchy of Lithuania; Trakai Castle Court acts; digital collections of Vilnius University Library; Slavonic languages of GDL